2010
DOI: 10.1016/j.clay.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The surface properties of clay minerals modified by intensive dry milling — revisited

Abstract: The present study broadened the research on the effect of the intensive physical disintegration of clay minerals (kaolinite and "Otay" montmorillonite) and mica (ripidolite), carried out by high-energy ball milling (HEBM), on their surface physicochemical characteristics, i.e., the specific surface area (SSA), the cation exchange capacity (CEC), and the electrokinetic properties. The mechanical disintegration of clay minerals occurred in two consecutive processes. Significant changes of the size, morphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 33 publications
3
42
0
1
Order By: Relevance
“…The transformation of clay minerals (kaolinite and chlorite-ripidolite) into fully amorphous particles of several tens of nanometers in size has been confirmed by milling experiments (Vdovic et al 2010), and such amorphous ultrafine particles have also been produced by friction experiments using quartzite, granite, and diorite (Yund et al 1990;Hirose et al 2012;Hirono et al 2013). The Chelungpu fault comprises three dominant fault zones , and the shallowest fault zone is most likely the one that slipped during the Chi-Chi earthquake because recent heating and a major stress-orientation anomaly were observed in that zone Wu et al 2007).…”
Section: Discussionmentioning
confidence: 81%
“…The transformation of clay minerals (kaolinite and chlorite-ripidolite) into fully amorphous particles of several tens of nanometers in size has been confirmed by milling experiments (Vdovic et al 2010), and such amorphous ultrafine particles have also been produced by friction experiments using quartzite, granite, and diorite (Yund et al 1990;Hirose et al 2012;Hirono et al 2013). The Chelungpu fault comprises three dominant fault zones , and the shallowest fault zone is most likely the one that slipped during the Chi-Chi earthquake because recent heating and a major stress-orientation anomaly were observed in that zone Wu et al 2007).…”
Section: Discussionmentioning
confidence: 81%
“…Gbureck et al reported that prolonged high-energy ball milling of β-tricalcium phosphate led to mechanically induced phase transformation from the crystalline to the amorphous state resulting in the thermodynamic solubility increase up to nine times and accelerated the normally slow reaction with water and such cements could reach the compressive strength up to 50 MPa [4]. The high-energy ball milling of clay minerals results in the decrease of the particle size (i); in significant increase of the specific surface area (ii); cation exchange capacity values (iii), and in the exposure of new, amphoteric surfaces, significantly changing the electrophoretic mobility while prolonged milling produced amorphous alumina-silicate aggregates (iv) [5]. Terada and Yonemochi indicated that the disintegration time of talc lead to decrease of the average particle size and increase of the specific surface area and also polar part of surface energy was increased by 41 % and hydrophilic surface was indicated [6].…”
Section: Introductionmentioning
confidence: 99%
“…Only if the material is capable of absorbing the energy can the internal structure of the substance be destabilized and new active surfaces be developed. 2 The effects of mechanical activation have been described for model materials such as dolomite 3 or clay minerals, [4][5][6] or, for example, for silica. 7 In the field of grinding and mechanical activation, research is focused on monitoring changes in the crystal structure and amorphization, 6,8 changes in the granularity and the aggregation and agglomeration of particles, 9,10 and changes in surface properties, especially the specific surface area and the zeta potential.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the field of grinding and mechanical activation, research is focused on monitoring changes in the crystal structure and amorphization, 6,8 changes in the granularity and the aggregation and agglomeration of particles, 9,10 and changes in surface properties, especially the specific surface area and the zeta potential. 4,8 One type of HEM is high-speed grinding (HSG). HSG involves supplying large amounts of energy using very short and intense power pulses.…”
Section: Introductionmentioning
confidence: 99%